The utilization of cloud-based servers in a college to optimize resource management - Putra, M Ruly (PT. Lentera Ilmu Publisher, 2024)
This article explores the transition of colleges from traditional physical servers to cloud-based servers to enhance resource management. As educational institutions seek to improve efficiency, scalability, and cost-effectiveness, cloud computing presents a promising alternative. By centralizing data storage, computing power, and network capabilities in the cloud, colleges can reduce physical infrastructure needs, lower maintenance costs, and optimize space utilization. Cloud solutions also offer advanced security features, crucial for protecting sensitive academic data. Despite these benefits, challenges such as data privacy, regulatory compliance, and the need for cultural adaptation within the institution must be addressed. Through a detailed assessment of existing IT infrastructure, stakeholder surveys, and pilot implementations, this study highlights how cloud-based servers can alleviate current inefficiencies and support a more sustainable resource management strategy. The findings suggest that transitioning to cloud services can significantly improve operational performance and stakeholder satisfaction, ultimately contributing to a more resilient and adaptable educational environment.